2022
DOI: 10.1002/jcla.24714
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0018189 drives non‐small cell lung cancer growth by sequestering miR‐656‐3p and enhancing xCT expression

Abstract: Background Non‐small cell lung cancer (NSCLC) is one of the cancers with a high mortality rate. CircRNAs have emerged as an important regulatory factor in tumorigenesis in recent years. However, the detailed regulatory mechanism of a circular RNA cullin 2 (hsa_circ_0018189; hsa_circ_0018189) is still unclear in NSCLC. Methods RNA levels of hsa_circ_0018189, microRNA (miR)‐656–3p, and Solute carrier family seven member 11 (SLC7A11, xCT) were analyzed by real‐time quantitative reverse transcription‐polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…MiR-656-3p is a tumor suppressor in cancers, such as nasopharyngeal carcinoma (20), liver cancer (21), and colorectal cancer (22). In NSCLC, downregulation of miR-656-3p counteracted the suppression of cell proliferation, glycolysis, invasion, and migration induced by circular RNA 0018189 deficiency (23). Additionally, miR-656-3p impairs NSCLC cell proliferation and migration (24).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-656-3p is a tumor suppressor in cancers, such as nasopharyngeal carcinoma (20), liver cancer (21), and colorectal cancer (22). In NSCLC, downregulation of miR-656-3p counteracted the suppression of cell proliferation, glycolysis, invasion, and migration induced by circular RNA 0018189 deficiency (23). Additionally, miR-656-3p impairs NSCLC cell proliferation and migration (24).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that multiple circRNAs can regulate SLC1A5 through their miRNA sponge role; therefore, the amino acid metabolism could be affected in non-small cell lung cancer [ 63 , 67 , 68 ], ovarian cancer [ 69 ], oesophageal cancer [ 62 ] and other cancer cells [ 70–72 ] ( Figure 4 ); and as the results, the development of malignant tumours would be promoted or inhibited. It has been found that circRNA can also promote the occurrence and development of non-small cell lung cancer by up regulating SLC7A11 of SLC family [ 73 ].
Figure 4.
…”
Section: Circrna and Cancer Cell Metabolic Reprogrammingmentioning
confidence: 99%